Penggunaan Model Cooperative Integrated Reading Composition (CIRC) Meningkatkan Kemampuan Membaca Pemahaman Di Sekolah Dasar - Muhammad Ilham; M. Syahrul Rizal; Rizki Ananda (UIR Press, 2022)
This study aims to improve the students' reading comprehension ability of Grade V Elementary School 020 Ridan Permai with children's stories. This study was dilated by the low reading comprehension results of fifth grade students in the 2021/2022 academic year as many as 15 subjects consisting of 14 male students and 14 female students. This research was conducted in two cycles, each cycle consisting of two meetings. Collecting data in this study using a test question instrument. Based on the results of data analysis, it can be seen that there is an increase in students' reading comprehension skills in Indonesian subjects. It only reached 53% then in the first cycle of meeting I increased to 62.5%, the first cycle of meeting II increased to 75% and the second cycle of meeting I increased to 83.3%, and the second cycle of meeting II increased again to 91.6%. Thus, it can be concluded that using the Cooperative Integrated Reading and Composition (CIRC) Model can improve the Reading Comprehension Ability of Class V students at SDN 020 Ridan Permai.